Housing policies and its impact on urban development in the Kingdom of Saudi Arabia during the period 1957-2021 - Al-Mudhyan, Areej Ali (Journal of Humanities & Social Sciences, 2022)
This study aimed to identify the Saudi experience in the housing sector by highlighting the housing policies that contained development plans during the period (1970 AD - 2020 AD), and highlighting the institutions and programs that support the housing sector during the period (1957-2021AD), in order to identify the housing policies that have encountered obstacles that have prevented the achievement of their desired objectives and to identify policies that have played a role in supporting the Kingdom's urban development. The study adopted a scientific approach based on (historical and descriptive approaches). Among the most important results it found: the low growth rate of the housing sector during the first development plan, which affected urban development; this decline is due to population migration towards cities, and the increase in land prices. The urban growth of housing occurred during the second development plan in places that do not correspond to the trend of urban growth with regard to cities, and the housing policies during the fourth development plan were able to achieve urban development, which resulted in meeting 60% of the volume of demand for housing during this period. The study made some recommendations, the most important of which are: working to increase the supply of serviced residential lands within the urban areas, and this is done through: Doubling the efforts of municipalities in extending services to all lands within the urban areas, thereby reducing the prices of serviced lands by increasing its supply. And to encourage the private sector to contribute to the increase the residential lands. It is worth pointing out here that this study is a summary of office and electronic data, and reports obtained from government agencies such as the Ministry of Housing, the Ministry of Economy and Planning, and the Real Estate Development Fund). This study is just a human endeavor that may be affected by deficiency and error. Perhaps the results and recommendations of this study will be used to support physical development.
Keywords: Housing policies; development plans; urban development; housing programs; Ministry of Housing